Survey of the Preliminary Inquiry in Canada - Pomerant, D; Gilmour, G (1993)
The paper also considers whether or not the procedure is in need of reform, or perhaps even abolition, given concerns that it contributes to delay and may unduly burden witnesses and victims. A Provincial Court judge has jurisdiction to hold a preliminary inquiry in some, but not all criminal cases; if an inquiry is held, it occurs between the first appearance of the accused and the trial. Its primary purpose is the screening out of weak or unmeritorious cases from the criminal process. This assessment of the preliminary inquiry identifies the restrictions imposed on the preliminary inquiry under current law and examines the scope of statutory duties allowed the presiding judge. To assess the role of the inquiry as a useful discovery mechanism, the paper also analyzes the recent "Stinchcombe" decision, in which the Supreme Court of Canada held that there must be full pretrial disclosure by the prosecution of all information relevant to the accused. In assessing the extent to which the law that governs the preliminary inquiry may need reform, the analysis examines reforms to the procedure in a number of Commonwealth countries and in the United States. The pros and cons of various reform proposals are presented. The paper concludes that the status quo is the least preferable option, given the disclosure requirements now applicable in Canada and the failure of the existing procedure to perform the function assigned to it. A 170-item bibliography and appended background information
OCLC: 4769405464